A study on the eye movement in people with low vision ‐ A case study in an eye clinic. Issue 4 (7th August 2019) - Matsuda, Yuji; Hara, Toshiaki; Kashiwase, Mitsutoshi; Nishide, Kazuhiko
Abstract: Eight people with low vision and eight people with no visual disability, each equipped with an eye‐mark recorder, were made to walk around the interior of an eye clinic in order to study the walking behavior and eye‐fixation behavior of people with low vision. Their actions and eye marks were recorded on video and their walking speeds and eye movements were compared. The results are as follows: (i) People with low vision tend to walk more slowly, directing their vision in many directions. (ii) People with low vision tend to look at the floor more, in particular, at the edges of the floor. (iii) People with no visual disability look at the target objects and use their peripheral vision while they walk, while people with low vision look more at the elements in their immediate environment while they walk. (iv) Environments with high contrast and continuous boundary surfaces that indicate walking directions are effective in making an interior environment easier for people with low vision to walk in. (v) For people with narrow visual fields or low visual acuity, composing the boundary surface so that it has a certain width increases the effectiveness of perception. Abstract : In this research, walking behavior and eye‐fixation behavior of people with low vision when they walk around the interior of an eye clinic are recorded and analyzed by using an eye‐mark recorder. The results are as follows: (i) People with low vision tend to walk more slowly, directing their vision in many directions. (ii) Environments with high contrast and continuous boundary surfaces that indicate walking directions are effective in making an interior environment easier for people with low vision to walk in.